Investigation on the antibacterial properties of Nanohydroxyapatite coated gutta-percha / Muhammad Firdaus Mat Saad - Muhammad Firdaus, Mat Saad (2019)
Introduction: Coating gutta-percha (GP) with a material similar to the component of dentine could expand it uses to most types of sealer as well as enhance the bonding to the root dentine. Al-Haddad et al. (2015) had invented nanohydroxyapatite coated guttapercha (HAGP) for root canal filling. The technology relates to the deposition of nanohydroxyapatite and tricalcium phosphate coating onto gutta-percha cones. This coating gives improved characteristics such as sealing ability, bonding strength, and ability to form hermetic seal as a root filling material in root canal treatments. However, the antibacterial property for the HAGP is yet to be analysed. Aim: This study was conducted to examine the antibacterial property of HAGP compared to the conventional GP. Methods: This study was divided into three parts: preparation of HAGP with biomimetic technique, gamma irradiation sterilization and screening of antibacterial properties. Escherichia coli (E. coli) and Enterococcus faecalis (E. faecalis) were used to conduct the antibacterial test. The coating involves the surface pretreatment of GP with sodium hydroxide and immersion of GP in simulated body fluid (Tas-SBF), which contains calcium and phosphate ions. These processes result in biomimetic deposition of a thin and uniform layer coating of calcium phosphates and hydroxyapatite. Subsequently, the prepared HAGP and conventional GP were sterilized using gamma irradiation with a dose of 13 kGy. The screenings of antibacterial activities were performed using agar diffusion assay and adherence assay at three time durations, 24, 48 and 72 hours. A total of three samples GP were used; conventional GP soaked in sodium hypochlorite (positive control), GP soaked in distilled water (negative control) and HAGP. In agar diffusion test, all samples were incubated on agar containing E. coli and E. faecalis for three different iv times to assess the formation of inhibition zone. In adherence assay, all samples were exposed in bacteria suspension for three different times. The colonization of bacteria were collected as colony forming unit (CFU) by serial dilution and droplet method. Results: Based on the antibacterial analysis, the data showed E. coli and E. faecalis were both susceptible against HAGP when compared to positive control (GP soaked in sodium hypochlorite). The data showed that HAGP produced no zone of inhibition when incubated with E. coli and E. faecalis, compared to positive control at 24, 48 and 72 hours. Moreover, the adherence study showed that the HAGP attracts more bacteria colonization compared to negative control. Based on the E. coli activity towards HAGP, the highest adherence capacity was found to be at 24 hours with significant differences (p < 0.05) when compared to negative control (GP soaked in sterile distilled water) and the percentage of adherence at 182.81% ± 49.13. The capacity of E. coli to adhere on HAGP was reduced from 48 to 72 hours with no significant difference in time (p > 0.05). However, the maximum adherence capacity for E. faecalis was at 48 hours (166.09% ± 3.56) and reduced at 72 hours (107.51% ± 6.42) with significant different in time (p < 0.05). Conclusion: The HAGP has no antibacterial properties against E. coli and E. faecalis. Therefore, it may not be the best to coat the GP with HA alone. Keywords: Hydroxyapatite, gutta-percha, antibacterial properties, E. coli, E. faecalis